2002
DOI: 10.1182/blood.v99.12.4265
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the molecular pathogenesis of follicular lymphoma arising from analysis of geographic variation

Abstract: Incidence rates of follicular lymphoma (FL) inexplicably vary markedly between Western and Asian countries. A hallmark of FL is the bcl-2 translocation, characterized by 1 of 2 common breakpoints known as major breakpoint region (MBR) and minor cluster region (mcr). We analyzed previously published data to compare rates of bcl-2 translocation in FL across geographic regions. Available data from the literature suggest that the incidence of bcl-2 in healthy persons in the absence of FL may be as high as 50% in W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
98
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 114 publications
(101 reference statements)
11
98
0
1
Order By: Relevance
“…Significant differences in molecular abnormalities are common in studies conducted across different continents, even in the same cancer type. 23,24 In this study, we had examined cases from United States and Chile, while Tannapfel's work was based solely on German cases. Secondly, there could be major epidemiological differences between the two sets.…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences in molecular abnormalities are common in studies conducted across different continents, even in the same cancer type. 23,24 In this study, we had examined cases from United States and Chile, while Tannapfel's work was based solely on German cases. Secondly, there could be major epidemiological differences between the two sets.…”
Section: Discussionmentioning
confidence: 99%
“…We searched the database of the Department of Hematopathology at The University of Texas MD Anderson Cancer Center, from 1 January 2000 to 30 June 2014, for cases of follicular lymphoma that were positive for CD5 as shown by flow cytometry immunophenotypic analysis or immunohistochemistry. A group of 99 patients with CD5-negative follicular lymphoma matched for age, gender, and stage were selected as a comparison group.…”
Section: Case Selectionmentioning
confidence: 99%
“…The reported distribution of NHL subtypes in India is different with those from the rest of the world [2]. In a study from India by Naresh et al [3] which incorporated immunophenotypic studies to investigate the distribution of NHL subtypes, FL was found to constitute about 12.6 % of all NHL.…”
Section: Discussionmentioning
confidence: 99%
“…Follicular Lymphoma (FL) is one of the most common B-cell non hodgkin lymphomas (NHL) accounting for 20-40 % in the western population [1,2]. The incidence is stated to be much lower in the Asian countries and about 12 % in the Indian population [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation